THE ROLE OF TAX REVENUE AND FOREIGN DIRECT INVESTMENT IN PROMOTING ECONOMIC PROGRESS IN NIGERIA - JOSEPH, Fineboy Ikechi; OMODERO, Cordelia Onyinyechi; OMEONU, Manasseh Obioma (Annals of Spiru Haret University. Economic Series, 2019)
Abstract The study examined the impact of tax revenue on economic growth of Nigeria proxied as gross domestic product (GDP) from 2000-2017). The study employed Exploratory and ex-post facto designs and secondary data sourced from Federal Inland Revenue Services (FIRS), UNCTAD, FDI/MNE database, World Bank Report, United Nations Development Programme (UNDP) reports, CBN statistical bulletin were used. Ordinary Least Squares (OLS) regression technique was adopted to test the hypotheses of the study. The result reveals that tax revenue has significant impact on GDP in Nigeria with R-squared showing that about 87% variations in GDP can be attributed to tax revenue, while the remaining 23% variations in GDP are caused by other factors not included in this model. This is further emphasized by the T-statistic p-value of 0.001 which shows that the regression result is statistically significant because it is less than 5%, level of significance adopted for this study. The result from regression analysis also revealed that there is positive relationship between foreign direct investment and Gross Domestic Product, with a p- value of + 0.000, + 0.001 < 0.05% significance level. The study concluded that tax revenue has a significant impact on GDP in Nigeria. Also there is a positive relationship between FDI and economic growth in Nigeria; therefore the more FDI increases the more economic growth. The study recommended that functional tax structures that would ensure that tax is collected from all taxable individuals, group of individuals and corporate bodies and remitted accordingly to the government without diversion should be instituted to widen the revenue base of the country. Government should liberalize the Nigerian economy the more by removing all barriers to trade such as arbitrary tariffs, import and export duties and other levies to encourage foreign investors.